NASA SEXTANT Mission Operations Architecture. (November 2020) - Yu, Wayne H.; Semper, Sean R.; Mitchell, Jason W.; Winternitz, Luke B.; Hassouneh, Munther A.; Price, Samuel R.; Ray, Paul S.; Wood, Kent S.; Gendreau, Keith C.; Arzoumanian, Zaven
Abstract: The Station Explorer for X-ray Timing and Navigation Technology (SEXTANT) mission is a technology demonstration enhancement to the Neutron Star Interior Composition Explorer (NICER) mission, a NASA Astrophysics Explorer Mission of Opportunity to the International Space Station (ISS) that was launched in June of 2017. The NICER instrument is a precision pointing X-ray telescope that tags pulsar sourced photon arrivals which the SEXTANT mission uses to perform autonomous on-board X-ray Pulsar Navigation (XNAV). By comparing the detected time of arrival of X-ray photons to a reference of expected pulsar timing models, one can infer a range and range rate measurement based on light time delay. Since the celestial source provides both timing and directional information, this technology could provide a GPS like navigation capability available throughout the Solar System and beyond. Applications that XNAV can support include outer planet and interstellar missions, manned missions, libration orbit missions, and current infrastructure such as the Deep Space Network (DSN). The SEXTANT team successfully completed a first demonstration of in-space and autonomous XNAV in November 2017. NICER and SEXTANT have separate teams, with NICER being the primary team with different science objectives. Operational modes for both missions must have concurrent and independent components as well as an integrated ground system. This paper describes the operational infrastructure and successful implementation of the SEXTANT demonstration. This paper first details the infrastructure implemented, the concept of operations, and finally the operations for the SEXTANT demonstration and lessons learned. Highlights: X-ray pulsar navigation: Use X-ray photons from stars to maintain orbit determination. NASA SEXTANT: First demonstration of on-board, real-time X-ray pulsar navigation. SEXTANT is part of the NASA International Space Station NICER X-ray telescope. SEXTANT operations implement tech demo with separate science/spaceflight operations.